2023
DOI: 10.1101/2023.03.08.23286986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of Hiv/HCV Coinfection Among People Living With Hiv/Aids Attending Federal Medical Centre, Yenagoa, Nigeria

Abstract: Coinfection of hepatitis C (HCV) may compromise antiretroviral therapy (ART) in Nigeria. In this study, we evaluated the seroprevalence of HIV/HCV coinfection in people living with HIV/AIDs (PLWHA) receiving ART and associated factors. Patients were selected from HIV-1-infected patients enrolled in National HAART Cohort at Federal Medical Centre in Yenagoa, Nigeria. Following the manufacturer's instructions, medical assessments and anti-HCV antibody serology were obtained for analysis with an ELISA kit (Dia. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…In terms of the immunological marker data, the highest HIV/HCV prevalence rate was 4.8% among individuals who had CD4 counts above 350. This observation is consistent with previous findings where the study participants with HIV/HCV co-infection had higher CD4 count (350-499 cells//µl) (Okonko & Shaibu, 2023). Ngwogu et al (2018) had a similar report of a higher prevalence of HCV among the respondents with a CD4 count greater than 350 (CD4 > 350).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of the immunological marker data, the highest HIV/HCV prevalence rate was 4.8% among individuals who had CD4 counts above 350. This observation is consistent with previous findings where the study participants with HIV/HCV co-infection had higher CD4 count (350-499 cells//µl) (Okonko & Shaibu, 2023). Ngwogu et al (2018) had a similar report of a higher prevalence of HCV among the respondents with a CD4 count greater than 350 (CD4 > 350).…”
Section: Discussionsupporting
confidence: 92%
“…., 2021). It may have infected up to 2%-3% of the world's population, making it a severe threat to health on a global scale(Okonko & Shaibu, 2023).This study was undertaken to determine the prevalence rate of hepatitis C virus (HCV) among people living with HIV (PLWHIV). The number of study participants enrolled was 255 HIV patients.…”
mentioning
confidence: 99%
“…As much as hepatitis C virus (HCV) infection is a serious global health concern, with estimates putting its prevalence between 2.0% and 3.0% of the global population (Okonko & Shaibu, 2023), the present study indicated a 0.0% HCV prevalence. Our observation is consistent with Okonko et al (2014) and Cookey et al (2021) who also reported a 0.0% prevalence in their studies.…”
Section: Discussionmentioning
confidence: 61%
“…Our observation is consistent withOkonko et al (2014) andCookey et al (2021) who also reported a 0.0% prevalence in their studies. The 0.0% infection rate with HCV contradicts the 4.0% byOkonko and Shaibu (2023) in Yenogoa, Bayelsa State, Nigeria andOketah et al (2024) in Awka, Anambra State, Nigeria; the 15.0% and 23.5% reported byOgbodo et al (2015) andOgwu-Richard et al (2015) in Nigeria. This 0.0% is also lower than the 0.5% in Lagos(Lawal et al, 2020), the 1.0% was recorded byAaron et al (2021) in Port Harcourt, Nigeria, the 0.5% in Anyigba(Omatola et al, 2019),…”
mentioning
confidence: 76%
See 1 more Smart Citation